Relaxed Asynchronous Iterations for the Linear Complementarity Problem (Journal of Computational Mathematics, 2002)
We present a class of relaxed asynchronous parallel multisplitting iterative methods for solving the linear complementarity problem on multiprocessor systems, and set up their convergence theories when the system matrix of the linear complementarity problem is an H-matrix with positive diagonal elements.
Keywords: Linear complementarity problem; Matrix multisplitting; Relaxation method; Asynchronous iteration; Convergence theory.